The influence of identity development on multicultural counselling competencies of counsellor trainees - Jee, Ng Kia; Ghazali, Nor Mazlina (Universitas Negeri Padang, 2020)
This study investigated the influence of the phases of identity development as identified by the Optimal Theory Applied to Identity Development (OTAID) framework on multicultural counselling competencies among the counsellor trainees in Universiti Malaysia Sarawak. This proposed research utilized correlational research design. 93 counsellor trainees were recruited for data collection by using purposive sampling. Three instruments were implemented in this study, which are Self-Identity Inventory (SII), Multicultural Awareness/ Knowledge/ Skills Survey (MAKSS), and Marlowe-Crowne Social Desirability Scale- Short (MCSDS-S).. The collected data were analyzed using Pearson Coefficient Correlation and Multiple Regression. The findings revealed that there is no relationship between identity development and multicultural counselling competencies. Likewise, no significant influence was found between identity development and multicultural counselling competencies. While Multicultural Skills did not predict by any phase of identity development, for no significant influence of identity development was found on Multicultural Skills.